Investigation of thermal tunable nano metallic photonic crystal filter with mirror symmetry - Zeinab Zare; abdolrasoul gharaati (Journal of Optoelectronical Nanostructures, 2018)
Using the transfer matrix method, the effect of temperature on thetransmission spectra of thermal tunable nano metallic photonic crystal filter has beeninvestigated. Three different materials H (high refractive index material), L (lowrefractive index material) and M as a metallic layer, have been used to make thisstructure. M layer is considered to be Silver. The complex refractive index of Silver is afunction of temperature and wavelength simultaneously so, the structure is tunable withtemperature and incident angle. It is found that the transmission peaks shift by changingtemperature and incident angle. At a given incident angle, they move toward higherwavelengths by increasing the temperature. The temperature dependence oftransmission peaks is linear. At a constant temperature, they move toward the shorterwavelengths by increasing the incident angle. Also by increasing the temperature, due todissipation